Sexting, Consent and Young People's Ethics: Beyond "Megan's Story" - Albury, Kath; Crawford, Kate (Continuum: Journal of Media & Cultural Studies, 2012)
This article contrasts the Megan’s Story campaign, a recent Australian media and policy response to sexting (the act of taking and transmitting naked or semi naked pictures via mobile phones) with interview responses drawn from an Australian study that has asked young people about mobiles and sexting. It considers local and international responses to sexting as ‘child pornography,’ raising questions about the adequacy and appropriateness of criminalizing young people’s sexual self representation and communication. Based on young people’s responses to sexting, the authors argue that there is an emerging ethics around the issue of consent being developed by young people. However, considerations of consent cannot be accounted for by the laws as they are presently framed, as under 18-year-olds currently are not allowed to consent to any form of sexting. This disconnection between the law and uses of technology by consenting teenagers generates problems both for policy, education and legal systems. This paper suggests a response that would recognize the seriousness of incidents of bullying, harassment or abuse, and would also take into account the meaning that sexting has for young people in specific contexts and cultures.